Infant mortality in the city of Belfast - Deeny, James; Murdock, Eric T. (Statistical and Social Inquiry Society of Ireland, 1944)
Within recent years attention in the North has been drawn to the high mortality rate in Belfast and, as a result, considerable interest in now being shown in the matter of child health. How serious is the situation can be appreciated from the fact that in Belfast each year, for every thousand children born, any number between 85 and 120 will die. The extreme danger of being a baby in this city is evident when it is realised that, in some years, one baby in every eight dies during the first year of life. Judging by standards existing elsewhere, 70 per cent, of these deaths are preventable and, consequently, at least five hundred children in Belfast lose their lives unnecessarily each year. To tackle such a problem, and it is being tackled, facts concerning every feature of the matter are required, and it is in this connection that we wish to present our study to the Society.
Read on Friday, 17th December, 1943
Keywords: Infant mortality; Belfast; 314.15